he effects of wild cherry & cumin on erythromycin- induced hepatic inflammation in diabetic rats. biochemical, histological & histochemical study. - Al shaikh, Mahera N.; Yas, Nawafal K.; hamdu, Hazim H. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: complications of diabetes have become more common as the rate of diabetes. This complication includes liver and diabetic autonomic neuropathly.